Pelanggaran Prinsip Kesopanan dalam Stand Up Comedy Bertajuk Somasi: Violation of the Principle of Decency in Stand-Up Comedy Titled Somasi - Sari, Ajeng Maulia; Kinanti, Kingkin Puput; Susandi, Susandi (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
The principle of politeness is one of the fields of study in pragmatics; Geoffrey N. Leech (1983) stated that pragmatics is the study of meaning in the context of various speech situations. Applying the principle of politeness is necessary in communication so that it can run well and correctly. However, sometimes, many people still do not comply with the principle of politeness for some interests, for example, in humor discourse, namely stand-up comedy. In stand-up comedy, violating the principle of politeness is something that comedians must do; this is done to present a funny impression to make the audience laugh. Considering comedians often commit many violations, researchers are interested in researching "Violations of the Principle of Politeness in Stand-Up Comedy Titled Somasi." This research study aims to analyze and describe the form and intent of violations of politeness maxims in a stand-up comedy titled Tomasi. The object of this research is the Somali videos uploaded on Deddy Combuzier's YouTube channel. This study uses a qualitative descriptive approach with the listening and note-taking method, where the researcher will transcribe every utterance that contains violations of politeness maxims carefully, thoroughly, and earnestly from every word or sentence expressed by the comedians that fall into violations of politeness principles. The results of this study show that in every video of the Somali program uploaded on Deddy Combuzier's YouTube channel, there are many types of violations of politeness maxims, such as violations of the maxim of tact, the maxim of acceptance, the maxim of generosity, the maxim of humility, the maxim of suitability and the maxim of sympathy.